Changes of Percent Body Fat as a Useful Surrogate for Risk of Declined Renal Function. Issue 1 (December 2018) - Chen, Yuan-Yuei; Fang, Wen-Hui; Wang, Chung-Ching; Kao, Tung-Wei; Chang, Yaw-Wen; Yang, Hui-Fang; Wu, Chen-Jung; Sun, Yu-Shan; Chen, Wei-Liang
Abstract The association between anthropometric indices with chronic kidney disease (CKD) was examined previously. However, the effect of body fat on renal function was not determined clearly. Our aim was to investigate the association of percent body fat (PBF) and renal function in adult population from health examination in Tri-Service General Hospital (2010–2016). 35087 participants aged 20 years and older were enrolled in the study. PBF was measured by bioelectrical impedance analysis (BIA). Estimation of renal function was performed by Taiwanese MDRD equation. Optimal cut-off values of PBF was accessed by a receiver–operator characteristic (ROC) curve analysis. Multivariate regression models were used in the relationship among changes of PBF, renal function, and future CKD. In terms of baseline PBF for CKD, optimal cut-off values of PBF in males and females were 21.55 and 40.75. The changes of PBF were more closely associated with renal function decline than waist circumference (WC) withβ values of −0.173 (95% CI: −0.233, −0.112) and −0.077 (95% CI: −0.104, −0.049), respectively. After stratified by gender, this relationship remained significant in male population withβ values of −0.276 (95% CI: −0.371, −0.181) and −0.159 (95% CI: −0.207, −0.112), respectively. Female subjects with increased baseline PBF over cut-off values had increased risk for predicting the future CKD with odd ratios (ORs) of 2.298 (95% CI: 1.006–5.252). Body fat had detrimental impact on renal function and development of CKD in adult population. Measurement of PBF for surveillance of renal function impairment was warranted.